2020
DOI: 10.1111/infa.12368
|View full text |Cite
|
Sign up to set email alerts
|

Using network analysis to capture developmental change: An illustration from infants’ postural transitions

Abstract: Network analysis is a tool typically used to assess interrelationships between social entities in a system. In this methodological report, we introduce how concepts from network analysis can be utilized to capture, condense, and extract complex developmental changes in individual behaviors over time. Using infant postural-locomotor de-928 | THURMAN ANd CORBETTA 1 | INTRODUCTION Development is a complex process, especially in infancy when change occurs rapidly. Further, individual infants influence and are infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Standing infants can more easily shift their positions or directions according to their communication partners. Thurman and Corbetta (2020) analysed infants' longitudinal data during free play and found that after infants learned to walk independently, they most often used standing postures to transition to other postures and became able to transition between postures more readily. These results suggest a high adaptability of standing postures for walking infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standing infants can more easily shift their positions or directions according to their communication partners. Thurman and Corbetta (2020) analysed infants' longitudinal data during free play and found that after infants learned to walk independently, they most often used standing postures to transition to other postures and became able to transition between postures more readily. These results suggest a high adaptability of standing postures for walking infants.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the kneeling and squatting postures were coded as the standing postures. However, Thurman and Corbetta (2020) showed that infants spent most of their time in kneeling and squatting postures while walking, and they discussed that these postures served as important bridges to other postures. Kneeling and squatting postures may have different functions from those of standing postures.…”
Section: Limitationsmentioning
confidence: 99%